How does embracing an outdoor lifestyle and sense of responsibility impact plastic reduction efforts? - Riordan, Oliver; Richter, Isabell (Frontiers in Sustainability, 2024)
Introduction Plastic pollution in coastal regions poses severe environmental challenges. This research aims to examine the impact of an individual's outdoor lifestyle and their perceptions of responsibility for litter management-specifically the roles of governments, businesses, non-governmental organizations (NGOs), Cornwall council, and volunteers-on their engagement in activities aimed at reducing plastic pollution. Methods The study surveyed 972 individuals in Cornwall, UK, to gather data on their perceptions and behaviors related to plastic reduction initiatives. The survey employed binomial logistic regression tests to analyse the relationship between respondents' views on responsibility for litter management and their participation in ten different plastic-reducing activities. Results The analysis revealed that individuals' perceptions of who should be responsible for managing litter significantly influence their likelihood of participating in plastic reduction activities. Notably, respondents who viewed national governments, businesses, and volunteers as responsible were more likely to engage in outdoor plastic reduction efforts, such as beach clean-ups. In contrast, attributing responsibility to the Cornwall council and NGOs was negatively correlated with participation in some plastic-reducing activities. Discussion The findings suggest that perceptions of responsibility play a crucial role in motivating individuals to participate in plastic reduction efforts. The positive correlation between viewing certain entities (governments, businesses, and volunteers) as responsible and increased participation highlights the potential for targeted interventions. Recommendations for enhancing plastic reduction participation include governmental policy changes, collaboration with outdoor sports groups, and the implementation of community-focused social marketing strategies to foster a collective sense of responsibility and action.